Mg–Ni–La based small hydrogen storage tank: kinetics, reversibility and reaction mechanisms. Issue 55 (8th September 2020) - Dansirima, Palmarin; Ngamwongwan, Lappawat; Suthirakun, Suwit; Utke, Oliver; Utke, Rapee
Abstract : De/hydrogenation performances and mechanisms of a Mg–Ni–La based H2 storage tank are investigated for the first time. Abstract : The improvement of de/rehydrogenation kinetics and reversibility of a Mg–Ni–La based small hydrogen storage tank by doping with TiF4 and MWCNTs is reported for the first time. During sample preparation, MgH2 milled with 20 wt% LaNi5 and 5 wt% TiF4 and MWCNTs produces Mg2 NiH4 and LaH3 . Two-step dehydrogenation of Mg2 NiH4 and MgH2 is detected at 295 and 350 °C, respectively. Hydrogen desorption and absorption of the tank complete within 150 and 16 min, respectively, together with reversible hydrogen storage capacity up to 4.00 wt% H2 (68% of theoretical value) upon 16 de/rehydrogenation cycles. Heat release from exothermic hydrogenation is removed effectively at the end of a double tube heat exchanger, where the reaction heat and heat transfer fluid are first in contact. Co-catalytic effects of Mg2 NiH4 and LaH3 as well as good hydrogen diffusion benefit dehydrogenation kinetics and reversibility of the tank.